Sosyal ağların şaşırtıcı gücü ve yaşantımızı biçimlendiren etkisi. - Güler Demir (Türk Kütüphaneciliği)
Connected: The Surprising Power of Our Social Networks and How They Shape Our Lives. While this book aims to provide a comprehensive picture of social networks, it also seeks to explore how they influence our lives and our lives are influenced by them. The theory suggesting that each person can be connected to every other person in the world through six interpersonal links is worth to be considered because many cases supporting it are included in the book. The book makes us rethink of our understanding of the notion of the individual and has a revolutionary paradigm, offering the idea that social networks influence our ideas, emotions, behavior, politics and even our health.